2017
DOI: 10.26737/jpmi.v2i2.226
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kelancaran Prosedural Matematis Siswa Pada Materi Persamaan Eksponen Kelas X Sma Negeri 2 Singkawang

Abstract: Abstrak. Penelitian ini bertujuan untuk mendeskripsikan kelancaran prosedural matematis siswa. Penelitian ini dilaksanakan di SMA Negeri 2 Singkawang. Jenis penelitian yang digunakan adalah kualitatif, bentuk penelitian yang digunakan deskriptif. Subjek penelitian adalah siswa kelas Xa SMA Negeri 2 Singkawang. Pengambilan data menggunakan instrumen berupa tes essay yang disesuaikan dengan karekteristik kelancaran prosedural matematis dan telah diujikan dengan validasi isi, validasi konstruk, reliabilitas, ting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
2
4
0
2
Order By: Relevance
“…With the theory of learning Bruner and Gagne and the opinion of NCTM, it is hoped that it can improve students' mathematical posedural fluency in FKIP UNSUR mathematics education students, so students can improve their achievements and support the achievement of other mathematical skills. This is the same as previous researchers which require reinforcement of procedural fluency (Valmoria & Tan, 2019), and also this is the same as researchers before where researchers concluded that students were instructed to be more careful again (Haryandika et al, 2017).…”
Section: Efficiencysupporting
confidence: 71%
See 1 more Smart Citation
“…With the theory of learning Bruner and Gagne and the opinion of NCTM, it is hoped that it can improve students' mathematical posedural fluency in FKIP UNSUR mathematics education students, so students can improve their achievements and support the achievement of other mathematical skills. This is the same as previous researchers which require reinforcement of procedural fluency (Valmoria & Tan, 2019), and also this is the same as researchers before where researchers concluded that students were instructed to be more careful again (Haryandika et al, 2017).…”
Section: Efficiencysupporting
confidence: 71%
“…Another study entitled Mathematical etudes: embedding opportunities for developing procedural fluency within rich mathematical contexts (Foster, 2013), procedural fluency was also tested on PTLSV material in terms of the learning style of Islamic boarding school students (Hartoyo & Suratman, 2018). Other researchers also tested procedural fluency in learning ALJABAR MATRIKS through the use of MAPLE (Setyansah & Masfingatin, 2017), other researchers tested by developing Scrabble media to improve procedural fluency (Kusumaningtyas & Yunianta, 2019), other researchers also analyzed procedural fluency in the material equation equation exponential (Haryandika, Utami, & Prihatiningtyas, 2017), other researchers also tested procedural fluency in Integer Operations (Valmoria & Tan, 2019), other researchers tested mathematical procedural fluency in solving marketing context problems (Fatimah & Zakiah, 2018), researchers others test procedural fluency in AIDS learning (Asmida, Sugiatno, & Hartoyo, 2018) Departing from this phenomenon, the researcher is interested in taking up this theme with the aim of analyzing and describing the mathematical procedural fluency of students when solving problems in numerical methods courses.…”
Section: This Includes Research Conducted By Fatimatul Khikmiyah and mentioning
confidence: 99%
“…Overall, the findings of this study indicate that the level of students' mathematical procedural fluency is still below the expected completeness criteria. These results are similar to those of Aprianti (2014), Haryandika et al (2017), andDamayanti et al (2018) who state that students' mathematical procedural fluency is still not fluent. However, in this study, the average percentage of the six self-regulated learning indicators observed was 72.92%.…”
Section: Description Of Students' Self-regulated Learningsupporting
confidence: 90%
“…However, some research results show the fact in the field that mathematical procedural fluency is still rarely considered in mathematics learning, so students have difficulty in mastering this skill. Aprianti (2014) and Haryandika et al (2017) in his research found that in the observed junior high school students there were no students who were included in the fluent category in applying procedures to fractional arithmetic operations. Asmida (2016) in his research, reported that only 68% of students had procedural fluency in the medium category in completing integer arithmetic operations.…”
Section: Introductionmentioning
confidence: 99%
“…Mahasiswa yang memiliki procedural fluency dengan kategori tinggi dan sedang masing-masing hanya sebanyak 5 mahasiswa (7,1%) dan 16 mahasiswa (22,5), sedangkan mahasiswa dengan kategori procedural fluency rendah berjumlah 50 mahasiswa atau 70,4%. Hasil ini sejalan dengan beberapa temuan lain yang juga menunjukkan kurangnya procedural fluency siswa dan mahasiswa (Haryandika et al, 2017), (Safitri & Lestari, 2022), (Novita et al, 2022). Siswa juga cenderung melakukan kesalahan prosedural dalam menggunakan prosedur pekerjaan (Lusiana, 2017).…”
Section: Hasil Dan Pembahasanunclassified